Microscopic polyangiitis: Clinical characteristics and long-term outcomes of 378 patients from the French Vasculitis Study Group Registry. Issue 112 (August 2020) - Nguyen, Yann; Pagnoux, Christian; Karras, Alexandre; Quéméneur, Thomas; Maurier, François; Hamidou, Mohamed; Le Quellec, Alain; Chiche, Noémie Jourde; Cohen, Pascal; Régent, Alexis; Lifermann, François; Mékinian, Arsène; et al.
Abstract: Objective: To describe characteristics and long-term outcomes of patients with microscopic polyangiitis (MPA), an antineutrophil cytoplasm antibody (ANCA)-associated small-vessel necrotizing vasculitis. Methods: MPA patients from the French Vasculitis Study Group Registry satisfying the European Medicines Agency algorithm were analyzed retrospectively. Characteristics at diagnosis, treatments, relapses and deaths were analyzed to identify factors predictive of death or relapse. Results: Between 1966 and 2017, 378 MPA patients (median age 63.7 years) were diagnosed and followed for a mean of 5.5 years. At diagnosis, the main clinical manifestations included renal involvement (74%), arthralgias (45%), skin (41%), lung (40%) and mononeuritis multiplex (32%), with less frequent alveolar hemorrhage (16%), cardiomyopathy (5%) and severe gastrointestinal signs (4%); mean serum creatinine was 217 μmol/L. ANCA were detected in 298/347 (86%) patients by immunofluorescence and/or enzyme-linked immunosorbent assay (ELISA). Among the 293 patients with available ELISA specificities, 272 (92.8%) recognized myeloperoxidase and 13 (4.4%) proteinase-3. During follow-up, 131 (34.7%) patients relapsed and 78 (20.6%) died, mainly from infections. Respective 5-year overall and relapse-free survival rates were 84.2% and 60.4%. Multivariable analyses retained age >65 years, creatinine >130 μmol/L, severe gastrointestinal involvement and mononeuritis multiplex as independent risk factors for death. Renal impairment was associated with a lower risk of relapse. Conclusion: Non-renal manifestations and several risk factors for death or relapse were frequent in this nationwide cohort. While mortality was low, and mainly due to treatment-related complications, relapses remained frequent, suggesting that MPA management can be further improved. Highlights: This large cohort of MPA patients had a high prevalence of non-renal manifestations. Age, renal insufficiency, gastrointestinal involvement and mononeuritis multiplex were risk factors for death. Renal impairment was associated with a lower risk of relapse. While mortality, mainly due to treatment-related complications, is rare, relapses remain frequent.